Redescription of Brachyolus punctatus White, 1846 (Coleoptera: Curculionidae: Entiminae), with synonyms and lectotype designations - Brown, Samuel D. J. (Zootaxa, 2018)
The New Zealand entimine weevil species Brachyolus punctatus White, 1846 is redescribed, with the following new synonyms proposed: Brachyolus albescens Broun, 1903, Inophloeus breviusculus Broun, 1880, Brachyolus elegans Broun, 1893 and Brachyolus viridescens Broun, 1893.